2006
DOI: 10.1007/s00421-006-0195-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term strength training for community-dwelling people over 75: impact on muscle function, functional ability and life style

Abstract: The objective was to determine the impact of a 1-year mixed strength-training programme on muscle function, functional ability, physical activity and life style. Twice-a-week hospital-based exercise classes and a once-a-week home session were conducted. Nineteen healthy community-dwelling training (T) men (76.6 +/- 3.1 years), 19 women (77.5 +/- 4.0 years) and 20 matched controls (C) participated in this study. Training was given with a two multi-gym machines for the lower limbs (Sitting calf and Leg press, TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
2
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 37 publications
9
52
2
6
Order By: Relevance
“…19 In a study investigating a battery of functional measures, older adults were found to improve their chair sit-to-stand by 28% and their stair climb time by 12%. 53 Other functional measures such as walking speed has also been shown to be increased up to 17% after a strength training intervention. 49 It is clear that strength training in older adults can result in numerous benefits, including increased muscle mass, increased muscle size, greater muscle fiber composition changes, and greater functional abilities whether a short-term or long-term, upper body, lower body, or total body exercises are implemented.…”
Section: Muscular Strength Training In Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In a study investigating a battery of functional measures, older adults were found to improve their chair sit-to-stand by 28% and their stair climb time by 12%. 53 Other functional measures such as walking speed has also been shown to be increased up to 17% after a strength training intervention. 49 It is clear that strength training in older adults can result in numerous benefits, including increased muscle mass, increased muscle size, greater muscle fiber composition changes, and greater functional abilities whether a short-term or long-term, upper body, lower body, or total body exercises are implemented.…”
Section: Muscular Strength Training In Older Adultsmentioning
confidence: 99%
“…Capodaglio et al found a 12% improvement in their time to climb stairs compared to control after one year of performing only two lower body exercises 3 times per week for 1 year. 53 However, when comparing strength training to power training (or high velocity training), the power group has greater improvements than strength training groups in functional measures such as the time to climb stairs compared to controls. For example, a group training using maximal movement velocity significantly improved their stair climb time after 8 weeks of training compared to control whereas the strength group performing slower velocity movements did not .…”
Section: Isokinetic Measuresmentioning
confidence: 99%
“…O TR isolado demonstrou ser relevante para a função de idosos (90% dos estudos) 23,[28][29][30][31][32][34][35][36] , sobretudo por seu decorrente ganho de força e mobilidade. O TR a longo prazo demonstrou ser desnecessário para ganhos funcionais.…”
Section: Funcionalidadeunclassified
“…Sob esse ponto de vista, a educação sobre a importância da atividade física é inerente ao envelhecimento saudável. Os TR de baixa 31 e moderada intensidade 29,32,34,35 também beneficiaram o desempenho funcional, especialmente nas idosas, frágeis e sedentários 29,31,35,45 . Isso sugere que a função não está ligada integralmente aos efeitos isolados da força, fato justificado pela observação em alguns casos, de um desempenho funcional satisfatório, mesmo com um ganho de força limitado.…”
Section: Funcionalidadeunclassified
“…The chair rise capacity was assessed by a timed chair rise test [5]. Participants were instructed to stand up five times from a chair as fast as possible, and their performance time was taken with a stopwatch with 0.1-second accuracy.…”
Section: Methodsmentioning
confidence: 99%